2017
DOI: 10.1152/ajpheart.00471.2016
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial interstitial levels of serotonin and its major metabolite 5-hydroxyindole acetic acid during ischemia-reperfusion

Abstract: By monitoring myocardial interstitial levels of 5-HT and its metabolite, 5-hydroxyindole acetic acid, we investigated 5-HT kinetics during myocardial ischemia-reperfusion. 5-HT accumulates but 5-HT degradation is suppressed during ischemia. After reperfusion, 5-HT degradation is enhanced and this degradation is dependent on monoamine oxidase activity but not fluoxetine-sensitive uptake transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…Furthermore, estimated 5‐HT turnover rate during reperfusion indicated that turnover of the accumulated 5‐HT was dramatically suppressed by the inhibition of PMAT. This effect was not observed by inhibition of SERT (Du et al, ), moreover it was similar to the effect of MAO inhibition by pargyline as we reported previously (Du et al, ). We have also demonstrated MAO‐dependent production of hydroxyl radical in the heart during ischemia and reperfusion (Inagaki et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, estimated 5‐HT turnover rate during reperfusion indicated that turnover of the accumulated 5‐HT was dramatically suppressed by the inhibition of PMAT. This effect was not observed by inhibition of SERT (Du et al, ), moreover it was similar to the effect of MAO inhibition by pargyline as we reported previously (Du et al, ). We have also demonstrated MAO‐dependent production of hydroxyl radical in the heart during ischemia and reperfusion (Inagaki et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…The first dialysate sampling was started from at least 2 hr after the probe implantation. Serotonin concentration in the dialysate sample was measured by electro‐chemical detection coupled with high performance liquid chromatography (HPLC‐ECD, Eicom) as described previously (Du et al, , ; Sonobe et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations